Environmental friendly application of ultrasonic rays for extraction of natural colorant from Harmal (P. harmala) for dyeing of bio-mordanted silk. (December 2021) - Adeel, Shahid; Rehman, Fazal-ur-; Zuber, Mohammad; Batool, Fatima; Habib, Noman; Hussaan, Muhammad; Amin, Nimra
Global heat, carcinogenic, and viral diseases created due to industrial pollutants has led people to shift toward natural products particularly natural dyes in all walks of life. In this study, U.S. rays up-to 60 min, were used to extract the color in aqueous medium and employed onto silk fabric at selected conditions. It has been observed that good color strength has been found when 30 mL of acidic extract ( p H = 4.0) obtained from 6.0 g of Harmal powder containing 3.0 g/100 mL of salt as an exhausting agent was employed onto the US treated silk at 65ºC for 55 min. The utilization of the extract obtained from 7% of pomegranate as post-bio-mordant, 3% of acacia extract as meta-bio-mordant, and 7% of henna extract as meta-bio-mordants has given excellent color strength. In comparison, 5% of Al salt as meta mordant, 5% of Fe salt as pre mordant, and 7% of tannic acid as meta-mordant has given better results. ISO standard methods for fastness employed onto optimum mordanted dyed fabrics have given well to excellent fastness ratings. Hence, natural colorant extracted from Harmal seeds has excellent coloring efficacy to dye silk fabric under sustainable conditions, whereas the addition of eco-friendly mordants for shade development process has made the coloration of silk more sustainable with improved colorfastness properties.